Tantangan Dan Harapan Pembelajaran Jarak Jauh Di Masa Pandemi Covid 19 - Masdaudi, Fitri Rahmah; Jamrizal, Jamrizal (Universitas Gajah Putih, 2024)
This study aims to reveal the extent to which distance learning during the Covid 19 pandemic has been effective and efficient, can distance learning achieve learning goals and can the figure of a teacher in the classroom be replaced with existing technology. Covid 19 the impact of the pandemic on education The existence of the corona virus has indeed hampered teaching and learning activities which usually take place face to face. However, there are major challenges in the implementation of the distance learning model. One of them, a teacher/lecturer is not used to using a mixed and fully online learning system.